2007
DOI: 10.1111/j.1471-0528.2007.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe twin–twin transfusion syndrome: outcome after fetoscopic laser ablation of the placental vascular equator

Abstract: Objective To assess the safety and efficacy of a modified fetoscopic laser ablation technique for the management of severe twin-twin transfusion syndrome (TTTS) in a large series of pregnancies.Design Prospective cohort study.Setting Tertiary referral fetal medicine unit.Population Women with pregnancies complicated by severe TTTS (Quintero stage III or IV), before 26 weeks of gestation.Methods Fetoscopic laser ablation of placental anastomoses was performed. The sonoendoscopic approach was used to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 35 publications
2
30
2
3
Order By: Relevance
“…One of the studies enrolled was a randomized controlled trial [13]; there were 13 prospective single-center cohort studies [10,12,18,19,20,22,23,24,25,26,28,30,32], 18 retrospective single-center cohort studies [27,29,31,33,34,35,36,37,38,39,40,41,42,43,44,46,47,59], 2 prospective multicenter cohort studies [21,58] and 3 retrospective multicenter cohort studies [45,48,55]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the studies enrolled was a randomized controlled trial [13]; there were 13 prospective single-center cohort studies [10,12,18,19,20,22,23,24,25,26,28,30,32], 18 retrospective single-center cohort studies [27,29,31,33,34,35,36,37,38,39,40,41,42,43,44,46,47,59], 2 prospective multicenter cohort studies [21,58] and 3 retrospective multicenter cohort studies [45,48,55]. …”
Section: Resultsmentioning
confidence: 99%
“…After full-text analysis a total of 34 studies were included in the time-based analysis [10,12,13,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. Twelve studies [5,49,50,51,52,53,54,55,56,57,58,59] presented data overlapping other series, of which one presented data relevant for the technique-based analysis [58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have reported a rate of cerebral lesions following laser of 5.4% [31]. In a series of 77 cases treated with coagulation of all vessels crossing the vascular equator [32], the authors considered the cerebral hemorrhage affecting 4 fetuses (2.6%) as preexisting because it was evident after AR at laser. Since our cases of cerebral damage occurred early on in our experience, we attribute them to the learning curve of the operators involved.…”
Section: Discussionmentioning
confidence: 99%
“…3,26,27 There is continuing debate on the selection and order which way the chorionic plate vessels should be coagulated, but is widely accepted that selective laser coagulation along the vascular equator should be attempted when feasible. [28][29][30][31] Selective feticide in complicated monochorionic pregnancies Selective feticide in monochorionic multiples cannot be performed by injection of potassium chloride or xylocain because the substance may embolise to the healthy fetus or the surviving fetus may exsanguinate via the ever-present anastomoses into the feto-placental unit. Vascular embolising agents were abandoned because of high failure rates, 32 probably because of incomplete vascular obliteration or product migration.…”
Section: Specific Instruments Used In Particular Indicationsmentioning
confidence: 99%